2014
DOI: 10.3109/08916934.2013.879862
|View full text |Cite
|
Sign up to set email alerts
|

Th17 and Treg cells in adolescents with Graves’ disease. Impact of treatment with methimazole on these cell subsets

Abstract: The role of T helper 17 (Th17) and T regulatory cells (Treg) in the pathogenesis of Graves' disease (GD) remains uncertain. The influence of methimazole (MMI) on the human immune system is still poorly understood. The aim of the present research was to assess changes in the frequencies of peripheral blood Th17 and Treg cells during GD treatment in the group of teenagers. The frequencies of Th17 and Treg were measured by flow cytometry in 60 adolescents at the time of GD diagnosis and after achieving MMI-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 30 publications
4
38
0
3
Order By: Relevance
“…It has been shown that Th17/Treg homeostasis was broken in multiple autoimmune diseases [13,14]. We and other investigators once conducted research on Th17 or Treg lymphocytes in GD or HT [15,16,17]. However, there has been neither study on Th17/Treg in GO nor a comparative analysis of Th17/Treg in different types of AITDs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Th17/Treg homeostasis was broken in multiple autoimmune diseases [13,14]. We and other investigators once conducted research on Th17 or Treg lymphocytes in GD or HT [15,16,17]. However, there has been neither study on Th17/Treg in GO nor a comparative analysis of Th17/Treg in different types of AITDs.…”
Section: Introductionmentioning
confidence: 99%
“…22 The peripheral blood was diluted 1:1 with a 0.9% phosphate-buffered saline (PBS) without calcium (Ca ) ions (Biochrome AG, Berlin, Germany). The diluted material was then overlaid on 3 mL of Gradisol L preparation (Aqua Medic, Łódź, Poland) with a specific gravity of 1.077 g/mL and subjected to density gradient centrifugation at 700 × g for 20 min.…”
Section: The Isolation Of Peripheral Blood Mononuclear Cells and The mentioning
confidence: 99%
“…The samples were gated on forward scatter vs side scatter to exclude debris and cell aggregates. 22 An example of a cytometric analysis is presented in Fig. 1.…”
Section: +mentioning
confidence: 99%
“…20, 3 2018 ется не только количество Treg в крови, но и на-рушается их функция. Подобное предположение также выдвигается рядом исследователей [7,15].…”
Section: иммунитет при болезни грейвсаunclassified
“…Обнаружено, что при БГ количество Treg в крови снижается [10,15]. При проведении тиреостатической терапии и нормализации концентрации тиреоидных гор-монов количество Treg в периферической крови больных повышается [6,7]. Однако механизмы Т-хелперной и регуляторной регуляции функ-циональной активности В-лимфоцитов при БГ раскрыты до сих пор не полностью.…”
Section: Introductionunclassified